Selected experiences with irrigation management transfer: Economic implications - Johnson, S.H. (1995)
After three decades of rapid increases in investment in irrigation systems, there has been an almost equally dramatic decline in irrigation investment, brought about by relatively low grain prices, rising construction costs and increased concern about the environment. As governments have been forced to reduce their public expenditures, many of them are now instituting programmes to transfer either complete or partial responsibility for management of public irrigation systems to local water users. This paper explores this transfer process in Indonesia, Colombia, New Zealand and Nigeria. From this sample it can be hypothesized that in countries where governments have had the political will to increase water fees to close to the real O&M cost, the process of irrigation management transfer has been smoother. This reflects the fact that water users are encouraged to take over management responsibility in order to reduce water costs. An equally important inducement for water users to accept additional management responsibility is better, more dependable delivery services from irrigation agencies.